Digital Library and Institutional Repository for Supporting Information Literacy - Munawaroh, ,; Prayitno, Dio Eka (Record and Library Journal, 2015)
Development of information technology, easy to get from smartphone or personal digital assistant (PDA) influence behavioral users to access information at library, that change behavioral users to access information effect of habit usersâEvery time with smartphoneâ. Example Users want to get information from book, they will copy or note but now they just take with their smartphone and access information from library they use laptop, gadget which connection internet. This condition a lot of librarian to develop their library became âDigital Libraryâ (DL) and âInstitutional Repositoryâ (IR). The goal of DL and IR are to provide information which more easy to access, especially local contents their institution. Exactly, not all libraries provide information of local contents not full text, just give information optional (abstract andsome chapter) or give information full text but just read only. The second menu at DL and IR not friendly with users and process retrieve too long time for founded. That phenomena users still contact librarian and came to library to access local contents. Digital Library (DL) and Institutional Repository (IR) is a collection in digital format for knowledge information sharing. The objective of this paper is to explain DL and IR as to assist sharing knowledge information for supporting information literacy at web institutions with explainÂ  contents full text local contents, user friendly searching services. This study used web-based of DL and IR institutions by searching on internet and it is qualitative descriptive.The judgment is based on whether the contents are fully texted or not fully texted. The fully texted indicates that the contents can support sharing knowledge or the other way around. It shows that the content of digital library and institutional repository for encouraging is to develop information literacy skill. It can be viewed from digital library and institutional repository as an alternative for supporting information literacy. It can be concluded that digital library and institutional repository must have information literacy